KARAKTER MORFOLOGI DURIAN (Durio ziberthinus M) LOKAL ASAL KABUPATEN KEPULAUAN MERANTI, RIAU - Eliartati; Rathi F. Zona; Saipul Hamdan (DINAMIKA PERTANIAN, 2023)
The purpose of this study was to determine the morphological characters of local durians in Rangsang Barat sub-district, Kepulauan Meranti district, Riau province. The study was carried out in Bokor Village, Rangsang Barat District, Kepulauan Meranti Regency, Riau Province from January to December 2019. The research was carried out using a survey method with exploratory descriptive techniques. The plant sampling technique was purposive random sampling using a non-probability sampling method. Determination of the sample based on the criteria of mature plants, age > 10 years, regular fruiting, having the required plant parts, and based on recommendations from the surrounding community. The observed characteristics included the appearance of the plant as a whole, leaves, flowers, fruits, and seeds. The results showed that the five local durians, Rangsang Barat sub-district, Kepulauan Meranti district, had different morphological characters, including tree morphological characters, leaves, flowers, seeds, and fruit. The advantages possessed by the five local durians are thick sweet taste (Durian Blewah), whole and dense fruit flesh per juring (Durian Calung), sweet taste of fat like nuts (Durian Kacang Pui), small and flat seed shape (Durian Kesep) and attractive flesh color (Durian Tembage).